Pedagogical de-construction: A moment for reflective practicum in the classroom. - Florez Villamizar, Libardo (Universidad Francisco de Paula Santander, 2014)
Society is becoming increasingly complex and browse a sea of uncertainty ; are multiple swing of daily life and even more when we add the changes and transformations that arise from technological innovations and to this phenomenon clothing society one of the key points on which falls most impact is without fear mistake education. Which is why the intention of this theoretical and practical approach is to focus its interest in reflecting on everyday pedagogical action from the perspective of deconstruction as a meaningful process to analyze the reflective practicum in the classroom and generate actions that converge in tools such as: tetralógico loop , cerebral gymnastics, sonidosofía, ecosophy and cognitive processes , among others; so that the teacher can make the teaching done in a creative, innovative , reflective, critical and proactive action and at the same time is achieved comprehend and understand the role of students or in the classroom. Indeed the proposed elements have positive and successful impact in pilot studies that have been conducted in some educational institutions where scientific rigor has been present within the research through the qualitative paradigm supported by the phenomenological - hermeneutic methodological approach. Pursuant to these provisions applicable in generating a harmonious classroom climate that nurtures knowledge and transform paradigms that hopefully in the not too distant future exit processes and reproduction of knowledge is achieved attain knowledge production and fit the demands of today's society that demands loudly transformer educational model that invites innovation and it complies with the needs of students who attend daily classroom in search of new horizons enabling them to draw on knowledge experience and knowledge to function in their.